2008
DOI: 10.1007/s11136-008-9383-9
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia: prevalence and its impact on excessive daytime sleepiness and psychological well-being in the adult Taiwanese population

Abstract: Taiwanese adults had a high prevalence of insomnia. Insomnia contributed at least partially to an individual's psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 18 publications
3
56
0
3
Order By: Relevance
“…Etwa in der japanischen Bevölkerung beträgt der Kurzschläferan-teil nur 4% (resp. : 3,2% Langschläfer) [5], in der taiwanesischen Bevölkerung lediglich 3,2% (zu lange Schlafdauer wurde hier nicht berichtet) [26].…”
Section: Schlafdauerunclassified
See 1 more Smart Citation
“…Etwa in der japanischen Bevölkerung beträgt der Kurzschläferan-teil nur 4% (resp. : 3,2% Langschläfer) [5], in der taiwanesischen Bevölkerung lediglich 3,2% (zu lange Schlafdauer wurde hier nicht berichtet) [26].…”
Section: Schlafdauerunclassified
“…Die Prävalenz in der deutschen Erwachsenenbevölkerung ist damit annähernd gleich hoch wie bei erwachsenen Personen in anderen Ländern [5,26]. Die Häufigkeit des Schlafmittelkonsums lag in der deutschen Erwachsenenbevölkerung bei insgesamt 5,7% und damit -trotz einer deutlich höheren Prä-valenz von Ein-und Durchschlafstörun-gen -vergleichbar hoch wie beispielsweise in der spanischen Bevölkerung mit 5,5% [27].…”
Section: Schlafqualität Und Schlafmittelkonsumunclassified
“…[1][2][3] In Taiwan, a study examining the prevalence rate of insomnia found that over 25% of Taiwanese adults experienced insomnia. 4 In Hong Kong, 39.4% of the adult population (equivalent to 2.2 million) are affected by insomnia. 5 It is recognized that, left untreated, transient insomnia can evolve to a chronic condition.…”
Section: Introductionmentioning
confidence: 99%
“…One-third of adults in the United States report inadequate sleep [2], and more than 25% of Taiwanese adults experience insomnia [3]. Sleep insufficiency can cause accidents; affect relationships and mental prowess; and have detrimental effects on health outcomes, such as increasing the risk for cardiovascular disease (CVD), type 2 diabetes mellitus (DM), obesity, cancer, depression, and total mortality [2,4].…”
Section: Introductionmentioning
confidence: 99%